2019
DOI: 10.1590/s1984-29612019009
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii and Neospora caninum infections in synanthropic rodents from Argentina

Abstract: Toxoplasma gondii and Neospora caninum are closely related coccidian parasites (phylum Apicomplexa). This is the first study from urban synanthropic rodent species that involved serological and molecular diagnosis of T. gondii and N. caninum infection, and genotyping of T. gondii in Argentina. A total of 127 rodent samples were trap captured: Mus musculus (n = 78), Rattus norvegicus (n = 26) and Rattus rattus (n = 23). Antibodies against T. gondii and N. caninum were detected by IFAT in 32.8% (40/122) and 0.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…It is revealed that naturally infected rodents can act as significant reservoir hosts and have a critical role in spreading T. gondii to other animals including pigs, dogs, and cats [ 23 ]. Our findings are comparable with those of Dellarupe et al from Argentina [ 25 ], Yan et al from China [ 23 ], Ahmad et al from Pakistan [ 26 ], Mosallanejad et al from Iran [ 27 ], and Salibay et al from the Philippines [ 28 ]. These studies found that the frequency of T. gondii in the rodent population was 32.8%, 23.9%, 11 to 58%, 24.41%, and 58%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…It is revealed that naturally infected rodents can act as significant reservoir hosts and have a critical role in spreading T. gondii to other animals including pigs, dogs, and cats [ 23 ]. Our findings are comparable with those of Dellarupe et al from Argentina [ 25 ], Yan et al from China [ 23 ], Ahmad et al from Pakistan [ 26 ], Mosallanejad et al from Iran [ 27 ], and Salibay et al from the Philippines [ 28 ]. These studies found that the frequency of T. gondii in the rodent population was 32.8%, 23.9%, 11 to 58%, 24.41%, and 58%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In this global systematic review, initially, 7,319 records were retrieved through principled search. After deleting duplicate records and screening, 24 studies were finally evaluated appropriate to be entered into this research (Araújo et al., 2010; de Lima et al., 2019; Dellarupe et al., 2019; Dubey et al., 2006, 2011; Galal et al., 2019; Herrmann et al., 2013; Howe & Sibley, 1995; Jokelainen & Nylund, 2012; Lehmann et al., 2003; Machačová et al., 2016; Muradian et al., 2012; Murata et al., 2018; Ruffolo et al., 2016; Silva et al., 2017; Vitaliano et al., 2014; Wang et al., 2013, 2018, 2019; Yai et al., 2009; Yan et al., 2014; Zhang et al., 2013, 2014; Zheng et al., 2019). Figure 1 demonstrates the details of the search and study selection procedure in a PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…They revealed that the frequency of Toxoplasma gondii in the Rattus norvegicus population in Argentina and China was 32.8% and 23.9%, respectively [24,25]. However, Pellizzaro et al in Brazil [8], Saki et al from Ahvaz province of Iran [10], Gennari from Brazil [9], and Cheng Yin from China [26] showed that the frequency of Toxoplasma gondii in Rattus population was 4.6%, 6%, 8.6%, and 3.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%